Association Between Computer Vision Syndrome And Attention In Workers - Arjuna, Sansan R; Ernawati, Titiek; Djaputra, Edith M (JOURNAL OF WIDYA MEDIKA JUNIOR, 2020)
Introduction: Nowadays, digital devices are rapidly growing and demanding everybody to use a computer or laptop for daily life, such as working, studying, playing games. Generally, the eye problem goes parallel with the growth of technology. Eyes problem related to the use of the computer, such as dry eyes, tired eyes, blurred eyes, and it is called Computer Vision Syndrome (CVS). Attention is a process that restricts much information that needs to be received and has a vital role in maintaining cognitive function. Attention is affected by the sensory stimulus, especially from the eyes. That is why CVS might influence attention. If the attention becomes distracted, it will affect studying or working performance. Aim: To analyze the association between CVS and attention in Workers. Methods: Cross-sectional is used in this research, and the sampling method was consecutive sampling. Computer Vision Syndrome Questionnaire and Trail Making Test part B is the instrument for this research Result: Respondents with CVS was 59,2%, disturbed attention was 63,2%, both CVS and disturbed attention was 40,8%. Chi-square trial showed p=0,110, which means that there is no association between CVS and attention. Conclusion: There is no association between CVS and attention in Workers.